Implikasi Pendidikan Kristen dalam Keluarga Menurut Efesus 6:1-4 Pada Masa Pandemi Covid-19 - Malau, Reynhard (Harati: Jurnal Pendidikan Kristen, 2021)
This study aims to see the implications of Christian education in families according to the text of Ephesians 6: 1-4 during the Covid-19 pandemic. In connection with the biblical text as an object, this research is classified as a type of descriptive research using an interpretive paradigm, more precisely called the interpretive descriptive method, by interpreting the text of Ephesians 6: 1-4, this method aims to build a theoretical framework that underlies interpretation, as well as describes the results of the analysis on the basis of findings which are clarified by theory. The results of this study are the implications of Christian education in the family according to the text of Ephesians 6: 1-4 during the Covid-19 pandemic, namely: improving the quality of the role of parents in the spiritual growth of children, as described in the exegesis of Ephesians 6: 1-4, growth. Spiritual children are the responsibility of parents, a child will respect their parents on the basis of fear of God, direction and education from parents which are also based on fear of God. Penelitian ini bertujuan untuk mengetahui bagaimana implikasi pendidikan Kristen dalam keluarga menurut teks Efesus 6: 1-4 pada masa pandemi Covid-19. Berhubungan dengan teks Alkitab sebagai objek, maka penelitian ini tergolong dalam jenis penelitian deskriptif dengan menggunakan paradigma interpretatif, lebih tepatnya disebut metode deskriptif interpretatif, dengan melakukan tafsir terhadap teks Efesus 6: 1-4, metode ini bertujuan membangun kerangka teori yang melandasi penafsiran, serta membeberkan hasil analisis atas dasar temuan yang diklarifikasi dengan teori. Hasil penelitian ini adalah implikasi pendidikan Kristen dalam keluarga menurut teks Efesus 6: 1-4 pada masa pandemi Covid-19, yaitu: meningkatkan kualitas peran orangtua terhadap pertumbuhan rohani anak, seperti apa yang telah dijabarkan pada eksegesis Efesus 6: 1-4, pertumbuhan rohani anak sudah merupakan tanggung jawab dari orangtua, seorang anak akan menghormati orangtuanya atas dasar rasa takut akan Tuhan karena arahan dan pendidikan dari orangtua yang juga didasari oleh rasa takut akan Tuhan.